The Role of Business Intelligence in Enhancing the Performance of Supply Chains in Jordan - Arikat, Zakieh Mahmoud Ahmad (Journal of Ecohumanism, 2024)
The study problem is represented by the question: What is the role of business intelligence in enhancing the performance of supply chains in industrial companies in Jordan?. A quantitative descriptive design was used in this study to explore the role of business intelligence in improving supply chain performance in Jordan. The study sample was selected using a stratified random sample. The expected number of participants in the study is 300 participants to ensure adequate representation of industrial companies in Jordan. The results showed that there is a positive role for business intelligence in enhancing the performance of supply chains (agility, integration, efficiency, customer responsiveness) in industrial companies in Jordan. The Jordanian companies are recommended to increase their investments in enhancing the performances of supply chains by adaption of business intelligence tools and technologies. In addition, it should focus on the development of human skills through training programs, which will definitely enhance employees’ capabilities to make better use of business intelligence technologies and data.